Pengaruh Suhu Ekstraksi dan Kecepatan Pengadukan terhadap Karakteristik Crude Ekstrak Stevia - Dewi, Luthfi Kurnia; Milenia, Rohmah; Islam, Livya Safira; Ismuyanto, Bambang (Jurnal Teknik Kimia USU, 2024)
Stevia is a natural sweetener that is 250-300 times sweeter than sucrose and is low in calories. Stevia sweeteners are obtained from the extraction of stevia leaves. This study aims to determine the effects of temperature and stirring speed on the characteristics of crude stevia extract (yield, brix value, and IR spectrum). Maceration extraction was conducted with 70% ethanol for 1 hour, varying the temperature (28 ℃, 40 ℃, 55 ℃) and stirring speed (0 rpm, 50 rpm, 100 rpm, 150 rpm). The results showed that a temperature of 40 ℃ produced the highest yield at each stirring speed. The yield increased with the increase in stirring speed at each extraction temperature. The highest brix value was obtained at 55 ℃ and a stirring speed of 150 rpm. The IR spectrum results showed that the functional groups in the crude stevia extract were almost identical to those in commercial stevia.